A Role for Biology in Gender-Related Behavior. - Berenbaum, Sheri; Blakemore, Judith; Beltz, Adriene (Sex Roles, 2011)
We take the opportunity of the 35th anniversary of Sex Roles to examine the journal and the field of gender research from a biological perspective. We discuss the limited coverage of biological perspectives in the pages of the journal and likely reasons for it in light of historical perspectives on the role of biology in gendered psychological processes and behaviors, review briefly contemporary research on biological (especially hormonal) influences on gender-related behavior, advocate for greater attention to biological perspectives, and suggest ways to integrate biological and socialization approaches into questions of interest to gender researchers.